Perfil epidemiológico do absenteísmo-doença em uma Instituição Pública de Ensino Superior no Rio Grande do Sul - Marques, Vera Regina (2017)
Study on Absenteeism-Disease (AD) among public servants of a higher education institution in Rio Grande do Sul. The study aimed to outline the epidemiological profile of this phenomenon, describing its frequency and the characteristics of the servants who were temporarily absent from work due to sickness in the study period. For this purpose, a descriptive study of quantitative approach was conducted to address temporary absence from work of servants in 2015 (n=404) that falls within the definition of AD. These servants generated 499 absences from work. The data obtained was stored in Excel spreadsheet and subsequently analyzed with SPSS statistical software. It was concluded that the most prevalent diseases in the referred period related to the longest periods of absence from work of the servants belonged to Groups M, F, S, I and C of ICD-10; Administrative Technicians (TAs) were more often absent from work than Professors; women were more often absent from work than men; the age group between 51-60 years showed the highest rate of absenteeism and the place where most servants were absent from work was the Central Campus. The high absenteeism rates among Administrative Technicians provide a warning sign of the need to investigate AD in the referred institution, in order to discuss work organization and adopt measures to prevent the sickening of the servants.